Combined CO2 and temperature effects on Emiliania huxleyi under severe nutrient stress - Borchard, Corinna (Universität Bremen, 2012)
Primary production in the sunlit surface ocean is the driving force for the uptake of atmospheric CO2 and basis for its potential sequestration into the ocean s interior. As a consequence of the ongoing anthropogenic emissions of the greenhouse gas CO2, future climate will cause multiple environmental changes in the global ocean, including acidification, warming and nutrient availability. This thesis deals with the synergistic effect of elevated CO2 and temperature at phosphorus limitation on organic matter production by Emiliania huxleyi. Experiments were accomplished by means of a fully controlled continuous culture facility, concerning the combined manipulation of nutrient supply, growth rates, CO2 and temperature. Cell density, particulate organic carbon (POC) concentration and cell size of E. huxleyi were affected to varying degrees by applied growth, CO2 and temperature conditions. Elevated CO2 and temperature (greenhouse scenario) clearly led to an extended plasticity of E. huxleyi concerning a minimum phosphorus cell quota. The ability to produce more organic matter on low nutrient supply most likely gives rise to the production of high amounts of carbon rich biomass characterised by high elemental C:N:P ratios. Emphasis was put on the impact of global change on the production of dissolved and particulate organic carbon, in order to gain a comprehensive understanding of the general partitioning between dissolved organic carbon (DOC) and POC. 14C incubations revealed that the partitioning between photosynthetically derived DOC and POC is highly dependent, not only on nutrient status and growth rate, but additionally affected by the combined rise of CO2 and temperature. Higher percentages of extracellular release (PER) were determined at lower growth rates and greenhouse conditions induced highest PER, thus the strongest partitioning to the dissolved pool. A major fraction of DOC is comprised by combined carbohydrates (CCHO) which are suggested to contain the pre-cursor molecules for aggregation and ...